2006
DOI: 10.1111/j.1440-1711.2006.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of carbohydrate in the interaction of Tamm‐Horsfall protein with complement 1q and inhibition of classical complement activation

Abstract: Tamm-Horsfall protein (THP) binds strongly to complement 1q (C1q), a key component of the classical complement pathway. The goals of this study were to determine whether THP altered the activation of the classical complement pathway and whether the carbohydrate portion of THP was involved in this glycoprotein's binding to C1q and alteration of complement activation. The ability of THP to prevent complement activation in diluted serum or plasma incubated at 37 degrees C was assessed using both a haemolytic assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…Deglycosylated THP (dTHP), THP that had approximately 88% of its carbohydrate moieties removed enzymatically,[21] was evaluated for C3b cofactor activity. As seen in Fig 10, THP (Lane D) and dTHP (Lane F) yielded a higher concentration of C3b α-chain fragments than were present in the C3b/CFI sample (Lane B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Deglycosylated THP (dTHP), THP that had approximately 88% of its carbohydrate moieties removed enzymatically,[21] was evaluated for C3b cofactor activity. As seen in Fig 10, THP (Lane D) and dTHP (Lane F) yielded a higher concentration of C3b α-chain fragments than were present in the C3b/CFI sample (Lane B).…”
Section: Resultsmentioning
confidence: 99%
“…Deglycosylated THP (dTHP), used in one set of C3b cofactor assays, was produced using a series of glycosidases on native THP where dTHP was separated from free carbohydrates as described previously. [21] It was estimated, by the change in mobility on SDS-PAGE, that about 88% of the carbohydrate was removed from dTHP and, by lectin blotting, that all of the sialic acid was removed. [21]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trapping role played by urinary THP may not be limited to cytokines. Previous in vitro studies suggested that THP also binds to complement C1 and C1q (61)(62)(63). It is possible that THP is a promiscuous urinary trap not only for cytokines, but also for other immunological effectors.…”
Section: Discussionmentioning
confidence: 99%